The Effect of Different Modalities of Mindfulness-Based Interventions on Blood Pressure - Ali AlKhabbaz; Batool M. Almusa; Edric D. Estrella (Jurnal Keperawatan Padjadjaran, 2022)
Background: Hypertension is one of the major killers around the world resulting in 7.6 million deaths and 92 million disability-adjusted life years (DALYs) per year (Lawes et al., 2001). Mindfulness-based interventions (MBIs) have been studied as nonpharmacological modalities of lowering blood pressure. However, the evidence about the different modalities of MBIs is still unclear. Purpose: The aim of this review is to identify the evidence about the effect of different MBIs on lowering blood pressure among different populations including hypertensive patients and healthy individuals. Methods: Pubmed, Cochrane Central Register of Controlled Trials (Ovid) and EBSCO databases were systematically used to search by using the keywords “(mindfulness) AND (blood pressure)”. All trials published from 1989 to July 2021 that reported the effect of MBIs on blood pressure as primary or secondary outcomes were included. Trials that did not report their results in English were excluded. Titles and abstracts were first screened for eligibility. Eligible studies were then fully reviewed and summarized. Results: A total of 53 research articles were included in this review with 3947 participants. They include patients with hypertension, cardiovascular diseases, obesity, cancer, stress, diabetes, pregnancy and healthy individuals. Articles were classified and sorted according to the modality of MBI used for better comparison. Conclusion: MBI modalities that are instructor guided and include breathing and/or physical exercises might result in a significant reduction of BP, especially among patients with HTN and/or anxiety. This effect could be complemented by other pharmacological and non-pharmacological interventions.